DYNAMIC AND ORGANISATIONAL SPECIFICS OF MEDICAL SERVICES FOR CHILDREN’S POPULATION IN KAZAN PROVIDED BY AMBULANCE PEDIATRIC CREWS - L.Z. Shakirova; E.A. Samorodnova; M.A. Malova (Педиатрическая фармакология)
The article provides analysis of the pediatric unit of the emergency call station in Kazan. Case-studied are 4,316 emergency calls over one month (April 2009). Structural and organisational specifics and level of emergency aid provided are assessed through a review of a number of indicators, particularly addresses of aided children assigning emergency call sites to areas covered by a specific sub-division, time spent, comparison against the standards, profile of the in-patient unit where a child was taken for hospitalization, etc. The results obtained allowed the authors to suggest measures to improve medical services for children’s population in the region.Key words: emergency call service, children.(Pediatric Pharmacology. – 2010; 7(4):86-89)